Comparative transcriptome analysis provides new insights into the response of common bean to infection by race 65 of Colletotrichum lindemuthianum - Caroline Marcela da Silva Dambroz; Alexandre Hild Aono; Larissa Carvalho Costa; Evandro Novaes; Welison Andrade Pereira (PLoS ONE, 2025)
The farming of common beans ( Phaseolus vulgaris ) is crucial for global nutrition, culture, and economy, but the crop faces significant challenges from biotic and abiotic stresses. Among these, anthracnose caused by Colletotrichum lindemuthianum , particularly race 65, is notable due to its widespread occurrence and high genetic and virulence diversity, especially in tropical regions such as Brazil. Understanding the molecular basis of resistance and susceptibility to specific pathogen races is key to accelerating the development of superior cultivars. Despite its significance, global gene expression studies addressing the interactions between bean genotypes and race 65 remain scarce. In this study, we explored the molecular basis of resistance and susceptibility to race 65 in two Brazilian common bean cultivars. RNA was extracted from leaves at 0, 48, and 96 hours after inoculation and sequenced using the Illumina NextSeq 500 platform. Our transcriptome analysis identified several candidate genes linked to resistance, including those involved in pathogen recognition, such as kinases and NB-LRR (nucleotide-binding and leucine-rich repeat) genes, as well as genes involved in the phenylpropanoid, glycerolipid biosynthesis, linoleic acid pathways, and cell wall remodeling. In contrast, the susceptible genotype exhibited activation of auxin signaling and sugar transport genes. Additionally, gene coexpression network analysis revealed a strong correlation among resistance-related genes. These findings provide valuable insights into the molecular-genetic mechanisms underlying common bean resistance to race 65 of C. lindemuthianum .